Understanding the outcomes of enterococcus faecalis and pseudomonas aeruginosa dual-species biofilms - Ong, Qian Wei (Nanyang Technological University, 2020)
Chronic wound infections are often polymicrobial in nature, resulting in complicated and dynamic interactions between wound microbes. Persistent wound infections are usually associated with biofilms and makes treatment more difficult through increase antibiotic resistance. In this study, we chose P. aeruginosa and E. faecalis, both are amongst the most commonly detected wound microbes, to investigate their interactions in dual-species co-culture. Preliminary data revealed co-culturing P. aeruginosa and E. faecalis in different ratios resulted in striking differences in biofilm production. We picked ratios PA1:EF1, PA1:EF100, and PA100:EF1 whereby a sharp increase or decrease in biofilm production was observed. It was hypothesized that the increase and decrease in biofilm production was linked to the viability of P. aeruginosa as the species was found to be the major producer in biofilm when in co-culture with E. faecalis. Thus, we conducted a cell viability assay. Our findings showed that E. faecalis inhibited P. aeruginosa viability in PA1:EF100 ratio, which corresponded to a decrease in biofilm production. While in other ratios, PA1:EF1 and PA100:EF1, P. aeruginosa was viable and the co-inhabitance of the two species strongly supports the synergism in biofilm production, confirming our hypothesis.